Pedestrian- & transit-oriented design - Ewing, Reid H.; Bartholomew, Keith; Burden, Dan.; Cloyton, Henry John.; Brown, Lauren; ProQuest (Firm) (Washington, D.C. : Urban Land Institute, 2013)
"Explaining how to design spaces for pedestrians while also accommodating transit needs, this book is an excellent reference for students, public sector planners and officials, and private sector designers and developers seeking to make places more pedestrian- and transit-friendly. Written by a noted expert on pedestrian design and planning, this handbook contains examples of zoning codes from different localities"--
Includes bibliographical references.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Pedestrian traffic flow -- Planning; Urban transportation -- Planning; City planning; Electronic books